The struggle for the past : how we construct social memories - Jelin, Elizabeth, 1941- (Worlds of memory ;, 2021)
"In all societies--but especially those that have endured political violence--the past is shifting and contested terrain, never fixed and always intertwined with present-day cultural and political circumstances. Organized around Argentine "memory wars" since the 1970s, 'The Struggle for the Past' undertakes an innovative exploration of memory's dynamic social character. In addition to its analysis of how human rights movements have inflected public memory and democratization in Argentina, it also gives an illuminating account of the emergence and development of Memory Studies as a field and critically reflects on the author's intellectual and humanitarian projects during this period"--